is this your homework ?
2007-02-09 04:53:21
·
answer #1
·
answered by sammy 5
·
0⤊
0⤋
2x + 3y = -3 and 3x - 2y = 28
Multiply the first equation by 3 and the second by 2 to cancel x:
6x + 9y = -9
6x - 4y = 56
Substract the second equation from the first:
9y - (-4y) = -9 - 56
13y = -65 or y = -5
Now substitute this in equation 1:
2x + (-15) = -3
2x = 15 - 3 = 12
x = 6
Check by substituting for x in equation 2:
3x - 2y = 28, 3X6 - (-10) = 18 + 10 = 28
So, the solution is correct and the values of x and y are 6 and -5 respectively.
2007-02-09 12:56:05
·
answer #2
·
answered by Swamy 7
·
0⤊
0⤋
2x + 3y = 3- - - - - -Equation 1
3x - 2y = 28- - - - - Equation 2
- - - - - - - - -
Multiply equation 1 by 2 and multiply equation 2 by 3
2x + 3y = 3
2(2x) + 2(3y) = 2(- 3)
4x + 6y = - 6
- - - - - - - - -
3x - 2y = 28
3(3x) - 3(2y) = 3(28)
9x - 6y = 84
- - - -- -- - - - --
4x + 6y = - 6
9x - 6y = 84
- - - - - - - - - -
13x = 78
13x/13 = 78/13
x = 78/13
x = 6
The answer x = 6
Insert the x value into equation 2
- - - - - - - - - - - - - - - - - - - - - - -
3x - 2y = 28
3(6) - 2y = 28
18 - 2y = 28
18 - 2y - 18 = 28 - 18
- 2y = 10
- 2y/ - 2 = 10 / - 2
y = 10 / - 2
y = - 5
The answer is y = - 5
Insert the y value into equation 2
- - - - - - - - - - - - - - - - - - - - - -
Check for equation 2
3x - 2y = 28
3(6) - 2(- 5) = 28
18 - (- 10) = 29
18 + 10 = 28
28 = 28
- - - - - - - - - -
Check for equation 1
2x + 3y = - 3
2(6) + 3(- 5) = - 3
12 + (- 15) = - 3
12 - 15 = - 3
- 3 = - 3
- - - - - - -
The solution set { 6, - 5 }
- - - - - - - - - - - - -s-
2007-02-09 14:23:43
·
answer #3
·
answered by SAMUEL D 7
·
0⤊
0⤋
2x+3y = -3 (1)
3x-2y = 28 (2)
It's best to use the elimination method because none of the coefficients are one.
Let's eliminate the y variable first:
The Lowest common multiple of 3 and 2 is 6, so
Multiply (1) by 2 and (2) by 3, we get:
4x+6y=-6
9x-6y=84
Add the two equations together:
13x=78
x=6
substituting x=6 into (1) or (2). I'll substitute into (1),
2*6 + 3y = -3
3y = -3 - 12
y = -5
2007-02-09 12:54:19
·
answer #4
·
answered by Yin H 2
·
0⤊
0⤋
This should be in homrework help I guess but....
Get x or y to have a common factor by multiplying one or both equations by something. In this case, it'd be both:
6x + 9y = -9
6x - 4y = 56
subtract and you get
13y = -65
divide both sides by 13 and y = -5.
Plug that into either equation:
3x + 10 = 28
so 3x = 18 and x = 6.
Check by plugging x and y into each equation:
12 - 15 = -3 OK and
18 + 10 = 28 !!!
So x = 6 and y = -5
2007-02-09 12:55:25
·
answer #5
·
answered by Meg W 5
·
0⤊
0⤋
2x+3y=-3...first equation
3x-2y=28...second equation
multiply the first equation by -3 and the second equation by 2
then you get
-6x-9y=9..first equation
6x-4y=56...second equation
then add up the two equations .. u get
-13y=65....remember -6x and 6x cancel each other
then -y=65/13
multiplay both sides by...(-)
then you get Y=-65/13.... which equals -5....then substitute y in one of the equation and find the value of x..
2x+3y=-3
2x+3(-5)=-3..when you move -15 to the right side its sign chages to positive 15.
2x=-3+15
x=12/2
x=6
there fore the solution set is x=6 and y=5
2007-02-09 13:52:48
·
answer #6
·
answered by Musteni s 1
·
0⤊
0⤋
There's a bunch of ways you can do that, but I like to use substitution.
1)Find the value of x in terms of y: 2x=-3-3y -- x=-3/2-3/2y
2)Substitute that in the other equation: 3(-3/2-3/2y)-2y=28
3)Solve for y: -9/2-9/2y-2y=28 -- -13/2y=65/2 -- y=-5
4)Solve for x: 2x+3(5)=-3 -- 2x=-18 -- x=-9
x=-9 and y=5
5)I will leave you to check for yourself
2007-02-09 12:55:21
·
answer #7
·
answered by NeRdYkId1101 3
·
0⤊
1⤋
4x + 6y = - 6
9x - 6y = 84 and now add
13x = 78
x = 6
24 + 6y = - 6
6y = - 30
y = - 5
2007-02-09 13:56:52
·
answer #8
·
answered by Como 7
·
0⤊
0⤋
x=6
y=-5
2007-02-09 12:59:36
·
answer #9
·
answered by m3th0dman n 2
·
0⤊
0⤋
Withdrawn - I made a little mistake.
2007-02-09 12:51:47
·
answer #10
·
answered by ecolink 7
·
0⤊
0⤋
i forgot how to do dat, but after seeing ecolink's answer i remembered....thanks....lol
2007-02-09 12:53:47
·
answer #11
·
answered by Anonymous
·
0⤊
0⤋